2019
DOI: 10.1177/2049936118820230
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin dosing in obese patients: analysis of the use of adjusted body weight versus actual body weight

Abstract: Background:Food and Drug Administration–approved daptomycin dosing uses actual body weight, despite limited dosing information for obese patients. Studies report alterations in daptomycin pharmacokinetics and creatine phosphokinase elevations associated with higher weight-based doses required for obese patients. Limited information regarding clinical outcomes with alternative daptomycin dosing strategies in obesity exists.Objective:This study evaluates equivalency of clinical and safety outcomes in obese patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…[97] Thus, dosing regimens, either fixed (500 mg/day), based on ideal body weight or based on adjusted body weight (calculated according to a function depending on actual and ideal body weights), have been proposed. [96,[98][99][100] Although it appears that the administration of fixed doses is most likely to lead to comparable exposures between obese and non-obese patients, this approach needs to be better evaluated and the determination of fixed doses to achieve effective exposure in obese patients remains to be done. [96] Furthermore, in order to make dose recommendations in obese patients, it seems important to measure the free fraction in this population.…”
Section: Pk In Special Populationsmentioning
confidence: 99%
“…[97] Thus, dosing regimens, either fixed (500 mg/day), based on ideal body weight or based on adjusted body weight (calculated according to a function depending on actual and ideal body weights), have been proposed. [96,[98][99][100] Although it appears that the administration of fixed doses is most likely to lead to comparable exposures between obese and non-obese patients, this approach needs to be better evaluated and the determination of fixed doses to achieve effective exposure in obese patients remains to be done. [96] Furthermore, in order to make dose recommendations in obese patients, it seems important to measure the free fraction in this population.…”
Section: Pk In Special Populationsmentioning
confidence: 99%
“…Two small retrospective studies observed similar treatment outcomes in obese patients with resistant gram-positive infections dosed on adjusted body weight (ABW) versus TBW. 28,29 Another retrospective analysis described similar clinical and microbiological outcomes in obese patients with gram-positive infections prescribed daptomycin dosed using ideal body weight (IBW) versus TBW. 30 Despite this, PK-PD analyses suggest that IBW-based dosing in obese patients results in suboptimal exposures compared with TBW-based dosing, whereas ABW (with a correction factor of 0.4) generated exposures only 6.6% higher than TBW-based dosing.…”
Section: Discussionmentioning
confidence: 99%
“…Dosing of daptomycin in patients with weight >100 kg has not been clearly established and can vary by site of infection, indication, and clinical pharmacist. In comparing adjusted with actual body weight dosing of daptomycin, there was no difference in clinical outcomes or CPK elevations in a retrospective review [ 9 ]. Our site changed from actual to adjusted body weight in our period of review, which impacted our ability to determine the effect of elevated BMI on eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Also, factors associated with the causes of eosinophilia (obesity and daptomycin dosing) have been inferred from case reports, but not clearly demonstrated [ 6 , 7 ]. With increased dosing of daptomycin to 8 mg/kg recommended for S. aureus infections, there has been no guidance on whether this should be on actual body weight (as recommended by the Food and Drug Administration [FDA]) or adjusted body weight, making it complicated for dosing in morbidly obese patients [ 8 , 9 ].…”
mentioning
confidence: 99%